Functionalized celluloses and their nanoparticles: morphology, thermal properties, and solubility studies - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Agricultural residues derived cellulose was used to synthesize a new series of carboxy functionalized cellulosic nanoparticles (quasi-spherical shaped, 13.2-21.5% carboxyl content) and macro-sized 6-carboxycelluloses (long-fibril shaped, 1.7-22% carboxyl content). The DP (50-70) and yield (upto 46%) of nanoparticles were manipulated by controlling the reaction temperature and time. TGA/DTG thermographs of the carboxycelluloses gave thermostability data and co-related well with the residual crystalline, amorphous, and anhydroglucuronic acid content. The particle shape and size had no effect on the thermal stability. Some derivatives were fully or partially soluble in aqueous alkali and non-aqueous solvents, which can lead to increased versatility of these polymers. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 6-Carboxycellulose; cellulose; DTG; Morphology; Nanoparticles; TGA

Thermal stability of cellulose and their nanoparticles: Effect of incremental increases in carboxyl and aldehyde groups - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Oxidized cellulose containing carboxyl and aldehyde functional groups represent an important class of cellulose derivatives. In this study effect of incrementally increasing COOH and CHO groups at C2, C3, and C6 positions of cellulose and nanocellulose has been investigated, with a view to understanding their effect on thermal treatment of cellulose. The results show that 2,3-dialdehyde cellulose (DAC) is the most thermally stable oxidized product of cellulose while the most unstable derivatives contain carboxyl group at the C6 position (6CC). Carboxymethylcellulose (CMC), with carboxymethyl group on C6 position, is more stable than 6CC. Multi-functionalized celluloses 2,3,6-tricarboxycellulose and 6-carboxy-2,3-dialdehyde, have the same level of thermal stability as 6CC, showing that the presence of carboxyl at the C6 is a key destabilizing factor in the thermal stability of oxidized cellulose products. More the number of reducing end groups on the polymer chain, lower the thermal stability of the cellulose, as proved by comparing the TGA/DTG of monomeric analogs dextrose, cellobiose and glucuronic acid with the oxidized celluloses. The thermal stability trend observed for oxidized celluloses was DAC > DCC > nanoparticles > dextrose >glucuronic acid, caused by extent of reducing ends and COOH groups. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 2; 3; 3-Dialdehyde cellulose; 6-Carboxycellulose; 6-Tricarboxycellulose; cellulose; TGA/DTG